The Effect of a Therapeutic Program for Genu Varum (Inward Bowing of the Legs) among Primary School Pupils Aged (6–7) Years - Jabr, Amir Abbas (Indonesian Journal of Education Methods Development, 2026)
General Background: Musculoskeletal deformities in early childhood may limit physical performance and participation in school activities. Specific Background: Genu varum (bow legs) in primary school pupils often causes discomfort, restricted movement, and reduced engagement in physical education. Knowledge Gap: Limited school-based rehabilitative programs have been systematically implemented and evaluated for young children with this condition. Aim: This study aimed to determine the outcomes of a structured eight-week rehabilitative exercise program with assistive tools for primary school pupils aged 6–7 years diagnosed with genu varum. Results: Findings indicated statistically significant reductions in knee and heel distance measurements, accompanied by improvements in speed and agility test scores across pre-, intermediate, and post-tests. Novelty: The study introduces a structured, school-context rehabilitation model integrating assistive tools with progressive corrective exercises tailored to young pupils. Implications: The program may serve as a practical framework for early detection and corrective intervention within primary school and community health settings. Highlights: Structured 8-week corrective exercise program for ages 6–7. Significant reduction in knee and heel distance measurements. Measurable improvements in speed and agility performance. Keywords: Genu Varum, Rehabilitative Exercises, Primary School Pupils, Physical Fitness, Corrective Program